2019
DOI: 10.5586/asbp.3621
|View full text |Cite
|
Sign up to set email alerts
|

Effects of invasive plant species on species diversity: implications on ruderal vegetation in Bratislava City, Slovakia, Central Europe

Abstract: Invasive species pose one of the most serious global environmental threats. Our study aimed to examine the correlation between the proportion of invasive alien taxa and species diversity of ruderal vegetation in the urban ecosystem of Bratislava, located in Central Europe. Ruderal habitats serve as the means of spread of invasive species to seminatural and natural habitats. Twenty-six invasive taxa were recorded among the ruderal vegetation of Bratislava. The majority of the recorded invasive species were neop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The cultural plants life is possible only in a certain temperature range, the upper and lower limits of which, so-called "critical temperatures" are given by the anatomical structure of the plant body and by the physiological processes in their organs. The temperature range over which the plants can develop and grow well varies and depends on the plant species and the areas in which they grow and from which they originate, as it was proven in the studies [Rendeková et al, 2019;Pozníková et al, 2018;Li et al, 2017]. Among the extremes, there is so-called "the optimum temperature band" that best meets the requirements of the plant organism at a given development stage.…”
Section: Introductionmentioning
confidence: 99%
“…The cultural plants life is possible only in a certain temperature range, the upper and lower limits of which, so-called "critical temperatures" are given by the anatomical structure of the plant body and by the physiological processes in their organs. The temperature range over which the plants can develop and grow well varies and depends on the plant species and the areas in which they grow and from which they originate, as it was proven in the studies [Rendeková et al, 2019;Pozníková et al, 2018;Li et al, 2017]. Among the extremes, there is so-called "the optimum temperature band" that best meets the requirements of the plant organism at a given development stage.…”
Section: Introductionmentioning
confidence: 99%
“…A comparable number was observed in, for example, the similarly sized city of Hradec Králové (the Czech Republic)—42 invasive neophytes [ 18 ]. However, in the much larger city of Bratislava (the capital of Slovakia), in ruderal areas alone, 26 invasive taxa were recorded [ 28 ]. Data collected by La Sorte et al [ 29 ] (Appendix S1) has shown that in other European capital cities even more invasive species have been found, e.g., Vienna (Austria)—141 (10.0% of city flora), Prague (Czech Republic)—138 (13.54%), Berlin (Germany)—121 (12.78%), Dublin (Ireland)—107 (19.7%), Rome (Italy)—213 (16.92%), Warsaw (Poland)—95 (17.96%).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the Asteraceae family is remarkably successful in terms of dispersal and establishment and is also the most abundant family of alien or invasive floras worldwide [52,53]. Species from this family are successful invaders not only in anthropogenic biotopes [54] but also in natural ones [55]. The family also hosts species most involved in pollenosis; one of which is Ambrosia artemisiifolia [56].…”
Section: Alpha Diversity and Species Compositionmentioning
confidence: 99%